Does Spiritual Leadership Matter for Enhancing Performance of Sharia-Compliant Hotel Employees in Aceh, Indonesia? Spiritual and Economical Motivation as Mediators - Murkhana, Murkhana; Idris, Sofyan; Abd. Majid, M. Shabri; Agustina, Maulidar (Faculty of Sharia and Law, UIN Syarif Hidayatullah Jakarta, 2023)
Abstract. This study explores the role of spiritual leadership in enhancing the spiritual and economic motivation and the performance of employees of Sharia compliant hotels in Banda Aceh, Indonesia. There are 330 employees of the selected Sharia-compliant hotels selected as the study's sample using a purposive sampling technique. The study found the important role of spiritual leadership in enhancing spiritual and economic motivation and employee performance. Additionally, spiritual leadership affects employees' performance indirectly through motivation. Thus, hotel management could improve employee performance by enhancing spiritual and economic motivation and spiritual leadership. Abstrak. Penelitian ini bertujuan untuk mengeksplorasi peran kepemimpinan spiritual dalam meningkatkan motivasi spiritual dan motivasi ekonomi serta kinerja karyawan hotel syariah di Banda Aceh, Indonesia. Sebanyak 330 karyawan hotel syariah telah dipilih sebagai sampel penelitian ini dengan menggunakan teknik purposive sampling. Penelitan ini menemukan peran penting kepemimpinan spiritual dalam meningkatkan motivasi spiritual dan motivasi ekonomi serta kinerja karyawan. Selain itu, kepemimpinan spiritual mempengaruhi kinerja karyawan secara tidak langsung melalui motivasi. Dengan demikian, manajemen hotel dapat meningkatkan kinerja karyawan dengan meningkatkan motivasi spiritual dan motivasi ekonomi serta kepemimpinan spiritual.